2
$\begingroup$

I'm trying to solve this problem, in particular part a. As the hint suggests I make the substitution $v=\frac{ds}{dt}$. Carrying out the computation I get $ln\frac{v}{V_0}=-KHe^{s/H}$, provided I haven't made any mistakes. Where do I go from here? How do I calculate the maximum deceleration?

EDIT: here is how I got $v$. By making the substitution $v=\frac{ds}{dt}$ we get $v\frac{dv}{ds}=-ke^{s/H}(v)^2$, hence $\frac{dv}{ds}=-ke^{s/H}v$, separating the variables $\frac{1}{v}dv=-ke^{s/H}ds$. Integrating $ln\;v=-kHe^{s/H}+c$, evaluating at $-\infty$ we get $c=ln\;V_0$.

$\endgroup$
  • $\begingroup$ @Aretino : I just wrote how I got $v$. Could you point out the mistake, please? $\endgroup$ – user113589 Feb 17 '17 at 7:49
  • $\begingroup$ You are right, sorry: your derivation is correct. You just have to insert your solution $v$ into the equation for $dv/dt$ and find the maximum of the resulting function of $s$. $\endgroup$ – Aretino Feb 17 '17 at 9:17
1
$\begingroup$

You correctly integrated the differential equation and found $$ \ln{ds/dt\over V_0}=-KHe^{s/H}, \quad \hbox{that is:}\quad {ds\over dt}=V_0\exp\big(-KHe^{s/H}\big). $$ Plugging that into the equation for the acceleration $a=d^2s/dt^2$ one then finds: $$ a=-Ke^{s/H}V_0^2\exp\big(-2KHe^{s/H}\big) =-KV_0^2\exp\left(-2KHe^{s/H}+{s\over H}\right). $$ Notice that $a\to0$ for $s\to\pm\infty$, so there must be a maximum value for $-a$, which can be found by solving the equation $da/ds=0$.This yields $$ -2Ke^{s/H}+{1\over H}=0, \quad\hbox{whence}\quad e^{s/H}={1\over 2HK}. $$ Now substitute that into the above expression for $-a$ to find the maximum: $$ (-a)_\max=K{1\over 2HK}V_0^2\exp\big(-2KH{1\over 2HK}\big)={V_0^2\over 2H e}. $$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Well, we have that:

$$\text{s}''\left(t\right)=-\text{K}\cdot\exp\left(\frac{\text{s}\left(t\right)}{\text{H}}\right)\cdot\text{s}'\left(t\right)^2\tag1$$

Treating $\text{s}$ as the independent variable, let $\rho\left(\text{s}\right)=\text{s}'\left(t\right)$:

$$\rho'\left(\text{s}\right)\cdot\rho\left(\text{s}\right)=-\text{K}\cdot\exp\left(\frac{\text{s}}{\text{H}}\right)\cdot\rho\left(\text{s}\right)^2\tag2$$

Now, solve the separable equation:

$$\frac{\rho'\left(\text{s}\right)}{\rho\left(\text{s}\right)}=-\text{K}\cdot\exp\left(\frac{\text{s}}{\text{H}}\right)\space\Longleftrightarrow\space\int\frac{\rho'\left(\text{s}\right)}{\rho\left(\text{s}\right)}\space\text{d}\text{s}=\int-\text{K}\cdot\exp\left(\frac{\text{s}}{\text{H}}\right)\space\text{d}\text{s}\tag3$$

So, we get that:

$$\ln\left|\rho\left(\text{s}\right)\right|=\text{C}-\text{H}\cdot\text{K}\cdot\exp\left(\frac{\text{s}}{\text{H}}\right)\tag4$$

So, we got two solutions:

  1. $$\text{s}'\left(t\right)=0\space\Longleftrightarrow\space\text{s}\left(t\right)=\text{C}_1\tag5$$
  2. $$\ln\left|\text{s}'\left(t\right)\right|=\text{C}_2-\text{H}\cdot\text{K}\cdot\exp\left(\frac{\text{s}\left(t\right)}{\text{H}}\right)\tag6$$
| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.